Antimicrobial activity of soil bacteria against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus - García Quishpe, Wendy Vanessa (2024)
The emergence of bacterial resistance to various drugs has made the search for new compounds a priority for the treatment of infections. It is estimated that there are between 100 million and 1 billion different types of bacteria with unique functions and roles. In one gram of soil there are millions of microorganisms that could produce metabolites with potential antimicrobial activity. Most reside in the top 20 cm of the surface horizon, which contains organic matter. Recent studies have focused on bacterial species that release antimicrobial compounds as possible therapeutic drugs to treat infectious diseases. Therefore, the aim of this work was to isolate and characterize antimicrobial-producing soil bacteria. For this study, bacteria present in the soil of Universidad de Investigación de Tecnología Experimental Yachay, were cultured and characterized. Antagonistic assays were performed between the bacterial isolates and Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The results obtained show that the metabolites produced by the isolated strains UITEY-030 and UITEY-055 inhibited the growth of Staphylococcus aureus and Escherichia coli strains, respectively.